Thermal Comfort and Occupant Perception at Residential Building in Kedah - Zulaikha, Siti; Abdul Razak , Amir Haziq; Sapari, Khairillizam (Progress in Engineering Application and Technology, 2024)
This study is to analyze the level and perception of occupants regarding the indoor comfort conditions in residential buildings. This study was conducted by using the questionnaire method to 248 respondents who occupied in residential buildings. This questionnaire measures various types of thermal comfort characteristics, including the current feeling of temperature and comfort in the room, assessment the effectiveness of the physical conditions in the room, occupant actions to improve comfort in the room, biological assessment, health effects from the discomfort of indoor conditions and acceptance of the overall comfort of indoor thermal in residential buildings. The data obtained was analyzed using SPSS to measure the occupants’ level of perception of the comfort of the interior conditions and to determine which rooms were most said to be very uncomfortable. The results of the study show that external factors such as direct sunlight into the room are the main factors of discomfort and spaciousness in the room that need to be taken into account between the equipment in the room and the number of occupants so that there is no overcrowding in the room.